Performance Audit Evaluation in the Implementation of Good Governance in Judicial Institutions (A Case Study of the Constitutional Court) - Maria Ulfah Kusuma Astuti (CV. Proaksara Global Transeduka, 2025)
This study aims to analyze the quality of performance audit, implementation of performance audit recommendations, and formulate an ideal concept of performance audit planning in order to strengthen the application of good governance principles at the Constitutional Court of the Republic of Indonesia. Motivated by the importance of performance audit as an instrument of supervision and enhancement of accountability of judicial institutions, particularly in constitutional case services. The research method used is a qualitative approach with a case study design. The unit of analysis in this study is the Constitutional Court of the Republic of Indonesia, with a focus on the Bureau of Law and Administration of the Registrar's Office as the unit that carries out the function of constitutional case services. Research data were obtained through in-depth interviews, documentation studies, and observation. Data analysis techniques were conducted using thematic analysis through the process of data reduction, data presentation, and drawing conclusions, and tested for validity using source and method triangulation. The study finds that while the Constitutional Court's performance audits meet established standards and yield relevant good governance recommendations, their implementation remains suboptimal. Specifically, follow-up actions, monitoring of internal evaluations, and the reinforcement of the internal supervisory apparatus require improvement. In response, the research formulates an ideal audit planning concept that is integrated, risk-based, and focused on the core constitutional case service process. These outcomes are expected to advance public sector audit scholarship and offer practical guidance for the Court to enhance its governance and service quality.